Investigation of thermophysical properties of ternary nitrate based phase change material induced with mxene as novel class of nanocomposites - Ilan Cheliyan, Samylingam (2021)
Concentrated Solar Power (CSP) technology has been identified as an alternate renewable and clean energy source. Thermal energy storage (TES) system which is vastly used in this technology requires good thermophysical properties for an optimum usage of the technology. Molten salt, an inorganic salt has been used as TES due its ability to operate at high temperature. Unfortunately, molten salt has high melting point and low thermal storage capacity. In this thesis, novel class nanocomposites containing ternary nitrate based molten salt induced with MXene is developed using two step method. LiNO3-NaNO3-KNO3 with the mass ratio of (35:10:55) and (35:12:53) are used as two pure ternary nitrate-based molten salt samples and doped with MXene in the wt.% of 0.2, 0.5, 1.0, and 1.5. Morphological and thermophysical properties of the new nanocomposites were studied using Scanning Electron Microscope (SEM), Energy Dispersive X-Ray Analysis (EDX), Fourier-transform infrared spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). SEM and EDX shows the mixture were properly mixed. DSC is used to measure the enthalpy and melting point of the prepared novel nanocomposites. The enthalpy of pure ternary molten salt of the mass ratio of (35:10:55) and (35:12:53) is increased by almost ≈5.74 times and 1.6 times, respectively, by doping 1.5 wt.% of MXene in each. TGA result showed that the samples were stable in the temperature range of 600 - 730 °C. With the addition of MXene, enhancement in specific heat can be seen. The highest cp value is found when 1.5wt% MXene is doped into LiNO3-NaNO3-KNO3 of 35:12:53 wt.% which is 1.84162 J/g.K. Developing the physiochemical parameters in the eutectic salts enhances its potential to be used as nanocomposite material and hence increases the efficiency of CSP.